Experimental diabetes exacerbates skin transplant rejection in rats - Reis,Flávio Pola dos (2013)
PURPOSE: To investigate the effect of chronic experimental diabetes on skin allografts in rats as a simple model that could clarify some basic aspects and mechanisms involved in transplant rejection in diabetes compared to normal animals. METHODS: Skin grafting was performed with fragments of tail skin from sex matched non diabetic Wistar rats engrafted onto the thoracic area of diabetic and non diabetic recipients. Grafts were scored for rejection every other day and were removed on day 14. Skin grafts were graded according to the following itens: no rejection; or rejection including: acute, chronic and humoral and/or cellular rejection. Statistical analysis was performed using JMP 5.1 software with ANOVA test. Diabetes was induced with IV injection of alloxan 40 mg/kg. RESULTS: Inflammatory vascular infiltrate compromising the endothelium with areas of fibrinoid necrosis and thrombosis characteristics of acute humoral rejection and subendothelial lymphocyte infiltrate typical of acute cellular rejection were significantly (p<0.003) higher in diabetic than in non diabetic recipients as the inflammatory infiltrate in the epidermis (p<0.002). CONCLUSION: Skin transplant acute rejection from chronic alloxan diabetic rats to normal tissue was significantly more intense than the acute rejection between normal rats.